Caring for the hospitalized child : a handbook of inpatient pediatrics - Gershel, Jeffrey C.; Rauch, Daniel A. (American Academy of Pediatrics, 2018)
"Fully revised and updated, the second edition of this popular point-of-care manual offers practical, authoritative guidance in the hospital setting for safe, effective inpatient care from initial evaluation through hospital discharge management. Pediatric hospitalists provide proven recommendations for various pediatric inpatient problems, including anaphylaxis; cardiac conditions; dermatologic, ENT and GI issues; infectious diseases; seizure; eye trauma; fractures; physical and sexual abuse; and much more"--Publisher's description